Evaluating the appropriateness of a community pharmacy model for a colorectal cancer screening program in Catalonia (Spain). (January 2017) - Santolaya, M; Aldea, M; Grau, J; Estrada, M; Barau, M; Buron, A; Francesc, M; Castell, A; Rodriguez, C; Gascón, P; Rius, P; Guayta-Escolies, R; et al.
Background: The traditional model of community pharmacy has changed, with patients, caregivers and consumers having access to many cognitive services other than the traditional dispensing and supply of medicines. In December 2009, a population-based colorectal cancer screening program started in Barcelona, introducing the community pharmacist and the professional expertise of the pharmacist into the organisational model. Aim: To evaluate the program implementation process in the pharmacies, identify barriers and facilitators, and know the opinion of the professionals involved in the colorectal cancer screening program in Catalonia (Spain). Methods: Cross-sectional study of the pharmacies that participated in the first round of the program during the first and second trimester of 2010 in Barcelona. A validated questionnaire was used to analyse several functional aspects in the implementation process. Qualitative aspects about the opinion of the pharmacist were studied. A descriptive and bivariate analysis was performed. Results: All the pharmacies involved in the program (n = 74) participated in the study. The majority of the sample population was composed of women (70.3%), mean age 44.9 years, and most of them (74%) had attended a specific training session. Pharmacists considered their participation in the program to be an added value to their professional role and a way to increase consumer's confidence on this kind of services. The average time to provide the service was estimated to be less than 10 minutes per consumer. Only three (4.1%) pharmacists considered that the program involved a lot of extra work in the daily activities of the pharmacy. The level of satisfaction of the pharmacists was very high. Conclusions: Community pharmacies can be a successful alternative and great resource to implement a population cancer screening program. This functional model can improve the accessibility and participation rates on target population. The level of motivation of the community pharmacist, the specific training program and the perception to give a better care for their patients can be an enabler.